Магнітні властивості наночастинок FeЗO4, одержаних рідинно- і твердофазним синтезом - Gorbyk, P. P.; Mishchenko, V. N.; Abramov, N. V.; Usov, D. G.; Troshchenkov, Yu. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The magnetic properties of the nano-particle of magnetite, obtained by the method of chemical condensation(ChC) and specially developed procedure of high temperature solid-phase synthesis (HTSPhS) are investigated. The technique of solid state synthesis of magnetite ncmoparticles based on decomposition to one or mixture of salts, containing Fe2+, Fe3+ ions and crystallization water, was proposed. The X-ray analysis, Transmission Electron microscopy and gas adsorption method were used Magnetic characteristics were studied by a vibration magnetometer. By the ChC method the dispersions of the particles Fe3О4 are collected medium-sized from 7,5 to 11 nm, by the HTSPhS method — medium-sized from 25 to 75 nm. It was shown that at the synthesis temperatures of 450-500 °C the single domain of Fe304 particles with specific magnetization saturation near to the maximum for magnetite value are formed.